Mechanisms of P* Reduction in the Eastern Tropical South Pacific - Meyer, Judith; Löscher, Carolin R.; Lavik, Gaute; Riebesell, Ulf (Frontiers in Marine Science, 2017)
Water masses influenced by oxygen minimum zones (OMZ) feature low inorganic nitrogen (N) to phosphorus (P) ratios. The surplus of P over N is thought to favor non-Redfield primary production by bloom-forming phytoplankton species. Additionally, excess phosphate (P*) is thought to provide a niche for nitrogen fixing organisms. In order to assess the effect of low inorganic nutrient ratios on the stoichiometry and composition of primary producers, biogeochemical measurements were carried out in 2012 during a research cruise in the eastern tropical South Pacific (ETSP). Based on pigment analyses, a succession of different phytoplankton functional groups was observed along onshore – offshore transects with diatoms dominating the productive upwelling region, and prymnesiophytes, cryptophytes and Synechococcus prevailing in the oligotrophic open ocean. Although inorganic nutrient supply ratios were below Redfield proportions throughout the sampling area, the stoichiometry of particulate organic nitrogen to phosphorus (PON:POP) generally exceeded ratios of 16:1. Despite PON:POP ≥ 16, high P* values in the surface layer (0-50 m) above the shelf rapidly decreased as water masses were advected offshore. There are three mechanisms which can explain these observations: (1) non-Redfield primary production, where the excess phosphorus in the biomass is directly released as dissolved organic phosphorus (DOP), (2) non-Redfield primary production, which is masked by a particulate organic matter pool mainly consisting of P-depleted detrital biomass, and/or (3) Redfield primary production combined with dinitrogen (N2) fixation. Our observations suggest that the three processes occur simultaneously in the study area; quantifying the relative importance of each of these mechanisms needs further investigation. Therefore, it remains uncertain whether the ETSP is a net sink for bioavailable N or whether the N-deficit in this area is replenished locally.